(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
Human Immunodeficiency Virus (HIV) has been a global health concern for several decades. While it primarily affects the immune system, HIV infection can manifest in various ways throughout the body, including the oral cavity. The oral manifestations of HIV can serve as clinical indicators of the disease’s progression and can significantly impact the quality of life of affected individuals. In this comprehensive article, we will explore the various manifestations of HIV infection in the oral cavity, the underlying mechanisms, the role of oral health professionals, and the importance of early detection and management.